Next step of molecular pathology: next-generation sequencing in cytology - Ricella Souza da Silva; Fernando Schmitt (Journal of Pathology and Translational Medicine)
The evolving landscape of precision oncology underscores the pivotal shift from morphological diagnosis to treatment decisions driven by molecular profiling. Recent guidelines from the European Society for Medical Oncology recomend the use of next-generation sequencing (NGS) across a broader range of cancers, reflecting its superior efficiency and clinical value. NGS not only updates oncology testing by offering quicker, sample-friendly, and sensitive analysis but also reduces the need for multiple individual tests. Cytology samples, often obtained through less invasive methods, can yield high-quality genetic material suitable for molecular analysis. This article focuses on optimizing the use of cytology samples in NGS, and outlines their potential benefits in identifying actionable molecular alterations for targeted therapies across various solid tumors. It also addresses the need for validation studies and the strategies to incorporate or combine different types of samples into routine clinical practice. Integrating cytological and liquid biopsies into routine clinical practice, alongside conventional tissue biopsies, offers a comprehensive approach to tumor genotyping, early disease detection, and monitoring of therapeutic responses across various solid tumor types. For comprehensive biomarker characterization, all patient specimens, although limited, is always valuable.